The Relationship between Heart Rate Recovery and Rate Pressure Product on Coronary Lesion Severity Using Syntax Score in Stable Angina Pectoris Patients at Haji Adam Malik Hospital Medan - Adam, Faisal; Andra, Cut Aryfa; Lubis, Hilfan Ade Putra (Journal of Society Medicine, 2024)
Introduction: RPP is used as a marker of cardiac function. RPP reflects the function of the heart in fulfilling oxygen demand stably and continuously during activity. Slow decline of HRR is associated with risk factors for atherosclerosis, similar to hypertension and dyslipidaemia There has not been much research on HRR and RPP in coronary heart disease. The aim of this study is to examine the relationship between RPP and syntax score in stable coronary heart disease. Methods: This study is an observational analytic study with a cross sectional design to determine the relationship between HRR and RPP to the severity of coronary lesions using the syntax score in stable angina pectoris patients. Sampling was carried out at the Haji Adam Malik Hospital Medan from February. HRR and RPP scores were obtained from cardiac exercise testing and syntax scores were obtained from coronary angiography after validation by an interventionist. EF data were taken from echocardiography results validated by consultant echocardiographers. Statistical data analysis using computer statistical tools, p value <0.05 was considered statistically significant. Results: From angiographic data in samples with syntax score ≥ 23, there were 23 (100%) LAD, 21 (91.3%) LCx, and 22 (95.7%) RCA involvement. In samples with Syntax score < 23, there were single vessel lesions as many as 11 (40.07%), two vessels as many as 12 (44.4%), and three vessels as many as 4 (14.8%). From the test results, there was a significant relationship between HRR and RPP and SYNTAX score with a p value <0.05 (<0.001) in both variables. Conclusion: There was a significant association in HRR scores and RPP scores between groups with SYNTAX scores ≥ 23 and SYNTAX scores < 23.